The yes factor : get what you want, say what you mean, the power of persuasive communication - Reiman, Tonya (Hudson Street Press, 2010)
Yes--a small word, but the key to opening doors both professional and personal. A "yes" can get you the job, the promotion, or the second date. But getting a "yes" can be tricky. Tonya Reiman explains how communication works--what the words you speak actually say about you, and how the perfect pitch can help you achieve your goals, convince your boss or client you should get the account, give a killer presentation, or win control of the remote (without ticking off your spouse!). Combining verbal and nonverbal tricks--identifying types of communicators, recognizing subconscious motivations, and adopting covert communication techniques--The Yes Factor is a simple approach to influencing and framing communication so that your message resounds clearly, ensuring that your ideas are implemented effectively and that you present your best possible self--From publisher description.